2001
DOI: 10.1021/tx010002c
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Binding of Acrylonitrile to Specific Rat Liver Glutathione S-Transferases in Vivo

Abstract: Acrylonitrile (AN) is an industrial vinyl monomer that is acutely toxic. When administered to rats, AN covalently binds to tissue proteins in a dose-dependent but nonlinear manner [Benz, F. W., Nerland, D. E., Li, J., and Corbett, D. (1997) Fundam. Appl. Toxicol. 36, 149-156]. The nonlinearity in covalent binding stems from the fact that AN rapidly depletes liver glutathione after which the covalent binding to tissue proteins increases disproportionately. The identity of the tissue proteins to which AN covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 50 publications
5
32
1
Order By: Relevance
“…Total protein recovery was 94%. SDS-PAGE analysis revealed the affinitypurified material to contain three closely spaced bands of apparent molecular mass around 25 kDa (Figure 2A), which is very consistent with previous observations (24,23). Direct When the same isolation procedure was applied to cytosol from [ 14 C]bromobenzene-treated rats, a similar result was obtained (Table 1B).…”
Section: Isolation and Characterization Of Rat Liver Glutathionesupporting
confidence: 90%
“…Total protein recovery was 94%. SDS-PAGE analysis revealed the affinitypurified material to contain three closely spaced bands of apparent molecular mass around 25 kDa (Figure 2A), which is very consistent with previous observations (24,23). Direct When the same isolation procedure was applied to cytosol from [ 14 C]bromobenzene-treated rats, a similar result was obtained (Table 1B).…”
Section: Isolation and Characterization Of Rat Liver Glutathionesupporting
confidence: 90%
“…GSHPx is responsible for the removal of ROS, such as peroxides, whereas GST is essential for conjugation. ACN may decrease the activities of these enzymes by defective synthesis or inactivation by binding [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo rat exposure and ex vivo studies on rat liver preparations highlighted binding to few specific proteins, identified as specific glutathione-S-transferase (Nerland et al, 2001) and carbonic anhydrase (Nerland, Cai, & Benz, 2003) isoenzymes. In these studies, derivatization of control and SCHEME 5.…”
Section: Reaction With Activated Olefinsmentioning
confidence: 99%